2000
DOI: 10.1002/1529-0131(200002)43:2<370::aid-anr17>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of rofecoxib (a cyclooxygenase 2 inhibitor), ibuprofen, and placebo on the gastroduodenal mucosa of patients with osteoarthritis: A randomized, double-blind, placebo-controlled trial

Abstract: At 2-4 times the therapeutically effective dose, rofecoxib caused fewer endoscopically detected ulcers than did ibuprofen. Rofecoxib at a dose of 25 mg (the highest dose recommended for osteoarthritis) satisfied prespecified criteria for equivalence to placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
1
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(146 citation statements)
references
References 19 publications
4
137
1
4
Order By: Relevance
“…Endoscopic ulcers were assessed in two OA studies 37,234 and one RA study 248 after up to 24 weeks of treatment. Cumulative incidences of ulcers were calculated using survival analysis methods, taking account of patient withdrawals.…”
Section: Endoscopic Ulcersmentioning
confidence: 99%
“…Endoscopic ulcers were assessed in two OA studies 37,234 and one RA study 248 after up to 24 weeks of treatment. Cumulative incidences of ulcers were calculated using survival analysis methods, taking account of patient withdrawals.…”
Section: Endoscopic Ulcersmentioning
confidence: 99%
“…Only three trials reported using a method of randomisation where allocation concealment could be assessed by the reviewers as 'adequate'. [88][89][90][91] Baseline characteristics appeared comparable in 14 studies, unclear in two studies and did not appear comparable in one study.…”
Section: Study Qualitymentioning
confidence: 99%
“…The COX-2 selective NSAIDs (coxibs) were developed to reduce damage to the gastrointestinal mucosa while offering effective analgesia and antiinflammatory action (5). In patients with OA, coxibs have an efficacy similar to nonselective NSAIDs (6), and in patients with OA and rheumatoid arthritis they reduce the risk of peptic ulcer disease and gastrointestinal (GI) bleeding (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%